The The Effect Of Service Quality And Visitor Motivation On Satisfaction And Intentions To Revisit At Bogor Botanical Garden - Sakti, Dimas Panca; I Nyoman Sudiarta; I Gusti Ngurah Widyatmaja (International Journal of Economics, Business and Innovation Research, 2025)
This research investigates the impact of service quality and visitor motivation on satisfaction and revisit intentions at Kebun Raya Bogor. Utilizing a quantitative explanatory approach, the study analyzes how these factors interact to influence visitor behavior. Through surveys with 100 visitors, the research identifies key dimensions of service quality—reliability, responsiveness, assurance, empathy, and tangibles—and evaluates how these, combined with visitor motivations, affect satisfaction and the likelihood of revisiting. The results indicate that both service quality and motivation significantly influence satisfaction, which in turn impacts revisit intention. This study highlights the importance of improving service quality to enhance visitor satisfaction and foster loyalty at tourism destinations.